Bearing behavior of high-performance concrete-filled high-strength steel tube composite columns subjected to eccentrical load - Jiang, Liangqin; Wang, Weichen; Ji, Jing; Ren, Hongguo; Wang, Qingqin; Sun, Ruohan; Yu, Chenyu; Zhang, Huiling; Luo, Gan (Frontiers in Materials, 2022)
In order to study the bearing capacity of high-performance concrete-filled high-strength steel tube (HCHST) composite stub columns subjected to eccentrical load, 22 HCHST composite stub columns, 4 concrete-filled steel tube (CFST) composite stub columns and 8 high-performance concrete-filled steel tube (HCST) composite stub columns were designed with the cubic compressive strength of concrete (fcu), the yield strength of steel tube (fy), the thickness of tube wall (t), the eccentricity (e) and slenderness ratio (λ) as the main parameters. Considering the nonlinear constitutive model of concrete and simplified constitutive model of steel, the finite element (FE) model of HCHST composite stub columns was established by ABAQUS software. By comparison with the existing test results, the rationality of the constitutive model and boundary conditions was verified. The variation of ultimate bearing capacity and the typical failure modes of HCHST composite stub columns under different parameters was analyzed. The results show that the specimens exhibit obvious bulge outward at the end of the steel tube and shear failure at the end of concrete. High-performance concrete (HPC) can significantly improve the ultimate eccentrical compression bearing capacity of composite columns, and high-strength steel tubes have better restraint effect on HPC. With the increasing of t, the ultimate eccentrical compression bearing capacity and the load-holding capacity of HCHST columns increases gradually, while the ultimate eccentrical compression bearing capacity decreases gradually with the increasing of λ and e. By introducing the reduction coefficient of eccentricity ("φ" _"1" ) and the reduction coefficient of slenderness ratio ("φ" _"2" ), the calculation formula of the eccentric bearing capacity of HCHST columns is proposed by statistical regression, which can lay a foundation for the application of HCHST columns in practical engineering.